Light Exposure Effects on Sleep Quality from Scientific and Hadith Perspectives: A Systematic Literature Review - Tia Putri Pratiwi; Luh Ade Yuanita Andriani (Jurnal Living Hadis, 2026)
More than just a daily activity, sleep holds many benefits for the body. This is shown by the hadith of the Prophet, particularly those related to sleep under certain conditions, such as the recommendation to turn off the lights. Furthermore, the research examines two problem formulations: first, how is the Prophet Muhammad's hadith about turning off the lights when sleeping interpreted from the perspective of maqāṣid al-syarī’ah and its relevance to modern scientific findings on sleep quality; and second, to what extent can the integration of hadith studies and contemporary scientific findings strengthen a holistic understanding of healthy sleeping practices? This study uses a systematic literature review with a PICO framework to formulate research questions clearly and purposefully for scientific and quasi-qualitative hadith studies, employing library research and thematic analysis of hadith. The findings of the study show that the hadith’s recommendation to turn off the lights when sleeping reflects the principle of maqāṣid al-syarī’ah, specifically the protection of life (hifz al-nafs), which is scientifically in line with scientific findings that darkness improves sleep quality through the regulation of circadian rhythms and melatonin production.